Analisis Manajemen Srategi Pengembangan Kurikulum Di SMP Yamis Jakarta - Neneng Humairoh; Zahruddin (Jayapangus Press, 2022)
Strategic management is one of the right choices in dealing with problems, because strategic management is management that is oriented towards the future and is based on the analysis of the internal and external environment. By following the process of strategic management stages, schools can consider decisions, follow-ups and the right choice of strategies in the face of the development and changes in the educational situation. This study aims to analyze the factors of curriculum development at SMP Yamis Jakarta using SWOT analysis to produce appropriate strategies and in accordance with applicable educational standards. Descriptive-qualitative research methods were used in this study. From this research, several factors were found that must be addressed in curriculum development, including the unclear focus of human resources and the lack of socialization in certain fields in curriculum development at the school and infrastructure that has not been maximized. Competition in the area of ​​intense education because it is surrounded by quality schools is a joint task in improving the quality of schools.